“Fiddling While Rome Burns”: The Role of Ecological States in the Association Between Greenhouse Gas Emissions and Subjective Well-Being - Signoretta, Paola; Bracke, Piet; Buffel, Veerle (Frontiers in Sociology, 2020)
In March 2019, students around the world took to the streets to express their anger at the lack of effective actions against the threat of climate change, essentially accusing governments and adults in general of “fiddling while Rome burns”. This paper puts forward the hypothesis that the ecological state moderates the positive association found in the literature between greenhouse gas emissions and mental wellbeing, taken as evidence of fiddling on climate change issues. This hypothesis is examined in the context of the countries and regions of the European Union using a hierarchical three-level analysis on the third wave (2011-2012) of the European Quality of Life Survey for a sample of EU citizens. The ecological state is operationalised using a climate change performance index. NO2 emissions data at the regional level are used as a measure of GHG emissions for regions of the European Union. The findings seem to support the hypothesis that individuals and governments keep ‘fiddling’ on climate change issues as a trade-off between environmental and economic considerations.